Organ procurement & preservation - Klintmalm, Goran B; Levy, Marlon F (Landes Bioscience, 1999)
Intended as a ready-reference guide for organ procurement and transplant units, the Handbook of Organ Retrieval and Preservation addresses the identification and management of potential donors and the subsequent retrieval and preservation of various organs. After an introduction to the historical development behind organ preservation, the authors discuss the physiological changes that take place in the organ donor and in an organ during preservation. Several preservation techniques are evaluated for their ability to minimize these physiological changes. In this handbook procurement coordinators, surgeons, residents and any other health care professionals involved in organ retrieval will find most questions answered that may arise during their participation with these difficult and complex issues. The Handbook of Organ Retrieval an d Preservation will prove an invaluable resource in the procurement or transplant unit as well as in the intensive care unit, where organ donors are potentially identified.
Keywords: transplantologie